Analysis of waste discharge concentration in radiative hybrid nanofluid flow over a stretching/shrinking sheet with chemical reaction - Mishra, Ashish (Mechanics of time-dependent materials, 2025)
This study examines the hydrothermal characteristics of hybrid nanofluid flow over a sheet in the presence of thermal radiation, chemical reaction, and waste discharge concentration to develop effective waste treatment and pollution control methods. The partial differential equations (PDEs) governing the conservation of mass, momentum, energy, and concentration, which are nonlinear, are transformed into ordinary differential equations (ODEs) using similarity transformations. The next stage in the process is to solve these differential equations using the bvp4c technique available in MATLAB. The study thoroughly explores several nondimensional parameters, including suction/blowing, Darcy number, stretching/shrinking parameter, local pollutant external source parameter, and chemical reaction parameter, visually illustrating their impacts on flow patterns, thermal distribution, and concentration profiles. The scrutiny focuses on key engineering parameters such as skin friction coefficient, heat transfer rate, and mass transfer rate, supported by tabular data that enhances the quantitative evaluation of these parameters. It is found that the velocity of hybrid nanofluid upsurges with the increment in the stretching/shrinking parameter and Darcy number. Also, results obtained reveal that the concentration profiles experience an upward shift with an increase in unsteadiness parameter and local pollutant external source parameter. Moreover, the Sherwood number decreases by 10.65% as the local pollutant external source parameter, ranging from 0.03 to 0.09, is increased.